Evaluation of Botanical and Chemical Insecticides against Jute Hairy Caterpillar (Spilosoma obliqua) in Mung Bean (Vigna radiata) in Rampur, Chitwan, Nepal - Joshi, Basu Dev; Gautam, Bhola; Adhikari, Chiran (Journal of the Plant Protection Society, 2024)
The jute hairy caterpillar (JHC) is a destructive, sporadic, polyphagous pest that requires timely management. This study, conducted in Rampur, Chitwan, Nepal, during the spring season of April 2022 to evaluate the efficacy of various insecticides against JHC through both laboratory and field experiments. In the laboratory, 3rd instar larvae were treated with ten treatments: chlorantraniliprole 18.5% SC, abamectin 5% EC, spinetoram 11.7% SC (each at 0.40 ml/L), essential oils of Mugwort, Lantana, and Neem (2.5 ml/L), leaf extracts of these plants (100 ml/L), and a water control. Larval mortality was recorded over 80 hours. Abamectin achieved 100% mortality within 56 hours, while chlorantraniliprole, spinetoram, Neem essential oil, and Neem leaf extract reached the same by 72 hours. Mugwort and Lantana leaf extracts showed similar efficacy to their essential oil extracts. The subsequent field experiment tested eight treatments (excluding leaf extracts of Mugwort and Lantana), applied four times at weekly intervals, starting 45 days after sowing. All treatments significantly reduced egg masses compared to the control, with no statistical difference between chemical and botanical insecticides. These findings suggest that botanical alternatives are as effective as chemical insecticides in reducing egg masses and larval populations, while also posing fewer environmental risks, making them a viable option for early-stage JHC management in the field. The 100% larval mortality observed under laboratory conditions suggests that all tested insecticides are also equally effective against the larval stage; however, further field research is needed to confirm this efficacy. Botanical alternatives thus offer a promising, eco-friendly option for early-stage JHC management.